Genome-wide transcriptional profiling of wheat infected with Fusarium graminearum - Kosaka, Ayumi (Genom Data, 2015)
Fusarium head blight (FHB) is a destructive disease in wheat caused by Fusarium graminearum (F.g). It infects during the flowering stage favored by warm and highly humid climates. In order to understand possible wheat defense mechanism, gene expression analysis in response to F.g was undertaken in three genotypes of wheat, Japanese landrace cultivar Nobeokabouzu (highly resistant), Chinese cv. Sumai 3 (resistant) and Australian cv. Gamenya (susceptible). For microarray analysis, 3 and 7 days after inoculation (dai) samples were used in Agilent wheat custom array 4x38k. At 3 dai, the highest number of genes was up-regulated in Nobeokabouzu followed by Sumai 3 and minimum expression in Gamenya. Whereas at 7 dai, Sumai 3 expressed more genes compared to others. Further narrowing down by excluding commonly expressed genes in three genotypes and grouping according to the gene function has identified differentially high expression of genes involved in detoxification process such as multidrug resistant protein, multidrug resistance-associated protein, UDP-glycosyltransferase and ABC transporters in Nobeokabouzu at 3 dai. However in Sumai 3 many defense-related genes such as peroxidase, proteases and genes involved in plant cell wall defense at 7 dai were identified. These findings showed the difference of molecular defense mechanism among the cultivars in response to the pathogen. The complete data was accessed in NCBI GEO database with accession number GSE59721.